ETYMOLOGY: WORDS THAT APPEARS IN THE LANGUAGE AND COMES FROM ANOTHER LANGUAGE AND ETYMOLIGICAL DOUBLETS (Ustozlar uchun, 2025)
This article examines the linguistic mechanisms behind etymology, loanwords, and etymological doublets, focusing on how languages develop through contact, borrowing, adaptation, semantic change, and historical convergence of word origins. Loanwords—lexical items adopted from one language into another—represent one of the most powerful forces behind vocabulary growth. Their phonological, morphological, and semantic integration illustrates the dynamic nature of linguistic evolution. Etymological doublets, which are pairs or groups of words sharing a common historical root but entering the language through different pathways, provide unique insights into language stratification, the chronology of borrowings, and semantic divergence. Through detailed analysis and examples from English (with occasional comparative notes from Russian and other languages), the article demonstrates how borrowed elements and their variants reflect cultural exchange, historical interactions, and internal linguistic restructuring.